Tracking the year-to-year variation in the spectral energy distribution of the narrow-line Seyfert 1 galaxy Mrk 335 - Tripathi S; McGrath K M; Gallo L C; Grupe D; Komossa S; Berton M; Kriss G; Longinotti A L (United Kingdom, 2022)
Multiwavelength monitoring of Mrk 335 with Swift between 2007 and 2019 are used to construct annual spectral energy distributions (SEDs) and track year-to-year changes. Non-contemporaneous archival data prior to 2007 are used to build a bright state SED. In this work, the changes are examined and quantified to build the foundation for future SED modelling. The yearly SEDs trace a downward trend on the average, with the X-ray portion varying significantly and acquiring further lower values in the past two years when compared to the optical/UV portion of SED. The bolometric Eddington ratios derived using optical/UV to X-ray SEDs and the calculated X-ray luminosities show a gradual decrease over the monitoring period. Changes in the parameters over time are examined. Principal component analysis suggests that the primary variability is in the X-ray properties of Mrk 335. When looking at the broader picture of Mrk 335 and its behaviour, the X-rays, accounting most of the variability in the 13-yr data, are possibly driven by physical processes related to the corona or absorption whereas the modest optical-UV variations suggest their origin within the accretion disc. These results are consistent with the previous interpretation of Mrk 335 using the timing analyses on the monitoring data and spectral modelling of deep observations....